Reflecting on Maine’s Changing Productive Coastal Region - Johnson, Teresa (Maine Policy Review, 2020)
This article reflects on Maine’s changing coastal region and blue economy. Much of Maine’s coastal economy is now considered to be overly dependent on a single commercial fishery, the iconic Maine lobster fishery. Marine aquaculture has grown in the last 10 years, with expansion expected both on land and sea. Marine renewable energy is also an emerging use but remains a frontier. These changes have been exacerbated by demographic changes characterized by youth out- and amenity migration. As community demographics and coastal uses continue to change following the region’s postproductive transition, policymakers must be proactive in considering potential conflicts emerging between different uses and value systems held in Maine’s coastal communities.
Keywords: marine aquaculture; commercial fisheries; marine renewable energy; blue economy